Quantitative Evaluation and Preoperative Planning Using Three‐Dimensional CT Profiles Improves the Accuracy of Bony Correction Under Primary Hip Arthroscopy and Clinical Outcomes in the Setting of Cam‐Type Femoroacetabular Impingement Syndrome - Feng Zheng; Wang Daofeng; Song Guanyang; Li Yue; Wang Xuesong (Orthopaedic Surgery, 2025)
ABSTRACT Objective Residual cam deformity is the main cause of revision hip arthroscopy, and the precise correction of cam lesions is a crucial clinical problem. This study aimed to propose a novel quantitative evaluation and preoperative planning method based on 3D‐CT profile analysis applied in primary hip arthroscopy for the treatment of cam‐type femoroacetabular impingement syndrome (FAIS) and to evaluate the effect of this method. Methods Consecutive patients who underwent primary hip arthroscopy for cam‐type FAIS between April 2018 and August 2022 were enrolled in this study. According to the method assisting cam resection, the included patients were divided into the planning group and the control group. Patients' demographic characteristics, preoperative radiographic measurements, and intraoperative procedures were collected. Preoperative and postoperative anterior α angle (Aα) and lateral α angle (Lα) were measured on 3D‐CT profiles, and the residual rates of anterior cam lesion (Ac) and lateral cam lesion (Lc) were calculated. Moreover, the 2‐year postoperative clinical outcomes, including clinical scores and achieving rates of clinically significant outcomes, were compared between groups. Results Eventually, the planning group included 68 patients and the control group included 57 cases. There were no significant differences in demographic characteristics, preoperative radiographic measurements, and intraoperative procedures between groups (p > 0.05). Postoperatively, the mean postoperative Lα in the planning group was significantly smaller than that in the control group (43.4° ± 9.5° vs. 60.8° ± 20.8°, p < 0.001). Correspondingly, patients in the planning group had a significantly lower rate of residual Lc (9.4% vs. 62.5%, p < 0.001) and overall residual cam lesion (14.7% vs. 54.4%, p < 0.001) compared to cases in the control group. At 2‐year follow‐up postoperatively, patients in the planning group reported significantly superior scores of mHHS (91.0 ± 6.0 vs. 86.3 ± 8.5, p = 0.001), iHOT‐12 (89.9 ± 7.2 vs. 82.7 ± 11.1, p < 0.001), and VAS for pain (1.2 ± 0.8 vs. 1.6 ± 1.1, p = 0.018) compared to patients in the control group. Moreover, the percentage of cases achieving patient acceptable symptom state (PASS) for mHHS in the planning group was significantly higher than that in the control group (97.1% vs. 84.2%, p = 0.012). Conclusions Quantitative analysis using 3D‐CT profiles is a reliable method for the evaluation of femoral morphology in patients with cam‐type FAIS. Additionally, preoperative planning based on 3D‐CT profiles can reduce the residual rate of cam lesions and improve short‐term clinical outcomes in these patients who underwent primary hip arthroscopy.